VSphere high performance cookbook : tune your vSphere to maximize its performance - Elder, Kevin; Sarkar, Prasenjit; Kusek, Christopher (Packt Publishing, 2017)
Over 80 recipes to help you improve vSphere 6.5's performance and solve problems before they arise About This Book The practical recipes provide cost-effective and high performance for any application running in a virtual machine Contains best practices and troubleshooting techniques to resolve vSphere 6.5 performance issues Get a comprehensive coverage of performance issues and solutions including vCenter Server design and virtual machine and application tuning Who This Book Is For If you are a system administrator and are planning to deploy vSphere 6.5 in your organization and want to maximize its performance, then this book is for you. Prior knowledge of the vSphere 6.5 concepts is essential. What You Will Learn Understand the VMM Scheduler, cache aware CPU Scheduler, NUMA aware CPU Scheduler, and more during the CPU Performance Design phase Get to know the virtual memory reclamation technique, host ballooning monitoring, and swapping activity Choose the right platform while designing your vCenter Server, redundant vCenter design, and vCenter SSO and its deployment Learn how to use various performance simulation tools Design VCSA Server Certificates to minimize security threats Use health check tools for storage and boost vSphere 6.5's performance with VAAI and VASA In Detail vSphere is a mission-critical piece of software for many businesses. It is a complex tool, and incorrect design and deployment can create performance related issues that can negatively affect the business. This book is focused on solving these problems as well as providing best practices and performance-enhancing techniques. This edition is fully updated to include all the new features in version 6.5 as well as the latest tools and techniques to keep vSphere performing at its best. This book starts with interesting recipes, such as the interaction of vSphere 6.5 components with physical layers such as CPU, memory, and networking. Then we focus on DRS, resource control design, and vSphere cluster design. Next, you'll learn about storage performance design and how it works with VMware vSphere 6.5. Moving on, you will learn about the two types of vCenter installation and the benefits of each. Lastly, the book covers performance tools that help you get the most out of your vSphere installation. By the end of this book, you will be able to identify, diagnose, and troubleshoot operational faults and critical performance issues in vSphere 6.5. Style and approach This cookbook ...